Flaxseed Prevents Leukocyte and Platelet Adhesion to Endothelial Cells in Experimental Atherosclerosis by Reducing sVCAM-1 and vWF - Raluca Ecaterina Haliga; Roxana Irina Iancu; Doina Butcovan; Veronica Mocanu (The Scientific World Journal)
We studied the possible effect of flaxseed to prevent leukocytes and platelets adhesion to endothelial cells and to reduce soluble adhesion molecules (sVCAM-1) and endothelial integrity markers (vWF) in ovariectomized rats fed a high-fat diet. Forty-two female Wistar rats were either sham-operated or ovariectomized and randomly assigned for 36 weeks to three different diets: (1) low-fat diet (8% energy as fat); (2) high-fat diet (40% energy as fat, lard based, lard group); (3) high-fat diet enriched with ground flaxseed 15 g/100 g of food (40% energy as fat, lard + flaxseed group). The ovariectomized rats fed with lard + flaxseeds had significantly lower serum concentrations of sVCAM and vWF, reduced platelet adhesiveness, and lower extent of platelet and leukocyte adherence to endothelium in the histological evaluation of the aorta as compared to Ovx + lard group. In our study, high dose of ground flaxseed incorporated to lard-based diet prevented the progression of atherosclerotic lesions in estrogen deficiency rats by decreasing platelet and endothelium reactivity. Assessment of platelet adhesion, serum soluble adhesion molecule sVCAM, and endothelium integrity molecule vWF could be useful to detect the risk for atherosclerotic lesions in estrogen deficiency states and to estimate the effect of flaxseed supplementation.